Implementation Measures of EU Strategy for Sustainable Tourism - Almeida, Paula (2021)
All over Europe it became clear that tourism is a cross-cuting economic activity with a wide-ranging impact on the environment and climate and on the EU´s economy as a whole. The tourism industry directly or indirectly employs 27 million people which accounts for 11.2% of total EU employment and helps to promote a positive regional development and contribute to the conservation of biodiversity, social welfare and economic security of local communities. As tourism and transport industries were among those most affected by Covid-19, as a result to restriction on travel, as a way to control the spreading of virus, it was clear that measures will be stronger as a part of a coordinated EU strategy. In this study we will approach the EU legislation that has been approved to create a common frame work for essential and non-essential travel, enabling the industry to adapt and apply compliant hygiene measures and the implementation in EU member states. Only by providing the EU and its Member States with a factual overview and data for policymakers, they will feel enable to devise informed strategies, based on collected and analysed tourism data.